Differential activation of placental unfolded protein response pathways implies heterogeneity in causation of early‐ and late‐onset pre‐eclampsia. Issue 2 (6th August 2014) - Yung, Hong Wa; Atkinson, Daniel; Campion‐Smith, Tim; Olovsson, Matts; Charnock‐Jones, D Stephen; Burton, Graham J
Abstract Based on gestational age at diagnosis and/or delivery, pre‐eclampsia (PE) is commonly divided into early‐onset (<34 weeks) and late‐onset (≥34 weeks) forms. Recently, the distinction between 'placental' and 'maternal' causation has been proposed, with 'placental' cases being more frequently associated with early‐onset and intrauterine growth restriction. To test whether molecular placental pathology varies according to clinical presentation, we investigated stress‐signalling pathways, including unfolded protein response (UPR) pathways, MAPK stress pathways, heat‐shock proteins and AMPKα in placentae delivered by caesarean section for clinical indications at different gestational ages. Controls included second‐trimester, pre‐term and normal‐term placentae. BeWo cells were used to investigate how these pathways react to different severities of hypoxia–reoxygenation (H/R) and pro‐inflammatory cytokines. Activation of placental UPR and stress‐response pathways, including P‐IRE1α, ATF6, XBP‐1, GRP78 and GRP94, P‐p38/p38 and HSP70, was higher in early‐onset PE than in both late‐onset PE and normotensive controls (NTCs), with a clear inflection around 34 weeks. Placentae from ≥ 34 weeks PE and NTC were indistinguishable. Levels of UPR signalling were similar between second‐trimester and term controls, but were significantly higher in pre‐term 'controls' delivered vaginally for chorioamnionitis and other conditions. Severe H/R (1/20% O2) induced equivalent activation of UPR pathways, including P‐eIF2α, ATF6, P‐IRE1α, GRP78 and GRP94, in BeWo cells. By contrast, the pro‐inflammatory cytokines TNFα and IL‐1β induced only mild activation of P‐eIF2α and GRP78. AKT, a central regulator of cell proliferation, was reduced in the < 34 weeks PE placentae and severe H/R‐treated cells, but not in other conditions. These findings provide the first molecular evidence that placental stress may contribute to the pathophysiology of early‐onset pre‐eclampsia, whereas that is unlikely to be the case in the late‐onset form of the syndrome. © 2014 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.